Trauma and Violence as Predictors of Internalizing and Externalizing Symptoms of Youth in Residential Child Welfare Placements - Farley, Tatjana M. (Journal of family violence, 2021)
Youth in residential treatment centers have high rates of internalizing and externalizing symptoms, and most youth in residential placements do not demonstrate long-term positive improvements in mental health. These youth also often experience high levels of exposure to violence and trauma, yet little is known about the interrelationships between exposure to violence, trauma, and mental health outcomes including internalizing and externalizing symptoms. As such, the primary purpose of this study was to determine the linkages between youth exposure to violence, trauma, and internalizing and externalizing symptoms. The current study examined these interrelationships and tested gender and race as moderators. The sample included youth in residential treatment with a mean age of 13.75 years, a diverse racial makeup, and almost an equal percentage of males and females. Trauma and exposure to violence were associated with internalizing and externalizing symptoms, and gender significantly moderated the relationship between trauma and externalizing symptoms, demonstrating a strong positive relationship for males in particular. Results highlight key associations between trauma and exposure to violence and youths’ internalizing and externalizing symptoms. Findings also revealed that gender moderated the link between trauma and externalizing symptoms with a positive association for males and a negligible association for females.